The Religious Dimensions of Advertising - Sheffield, T. author. aut Link
XVI, 190 p.
Keywords: This groundbreaking work explores media scholar Sut Jhally's thesis that advertising functions as a religion in late capitalism and relates this to critical theological studies. Sheffield argues that advertising is not itself a religion, but that it contains religious dimensions - analogous to Durkheim's description of objects as totems.